ПЕРСПЕКТИВАТА НА ПРЕМЕСТЕНОСТА ВО МУЗЕЈ НА БЕЗУСЛОВНОТО ПРЕДАВАЊЕ И ВО МИНИСТЕРСТВО НА БОЛКАТА ОД ДУБРАВКА УГРЕШИЌ (Philological Studies, 2019)
In his essay Reflections on Exile, Edward Said points that, while “most people are principally aware of one culture, one setting, one home; exiles are aware of at least two, and this plurality of vision gives rise to an awareness of simultaneous dimensions, an awareness that – to borrow a phrase from music – in contrapuntal”. This text examines this contrapuntal awareness of the characters from the novels The Museum of Unconditional Surrender and Ministry of Pain by Dubravka Ugrešić.
Keywords: Dubravka Ugrešić, loss, homeland, language, identity, culture, dislocation, exile